Managing know-who based companies : - Harryson, Sigvald (E. Elgar Pub., 2002)
This book is recommended reading for CEOs of multinational companies who wish to make better use of the value networks in which they live and do business. It will also be of significant value to CTOs, CKOs and Human Resource Managers interested in new ways to turning both hard technologies and soft human brainpower within and beyond the corporate borders into faster and more powerful innovation.